Taxonomic notes on Oriental bamboo-shoot fruit fly genus Acroceratitis Hendel (Diptera: Tephritidae: Dacinae: Gastrozonini), with description of a new species from India - David, K. J.; Mahammed, N. R. Noor; Hancock, D. L.; Gracy, R. G.; Ningthoujam, Kennedy; Sushil, S. N. (Zootaxa, 2025)
A new species of Acroceratitis Hendel, namely Acroceratitis sachini David, Hancock & Noor is described from Western Ghats, Karnataka, India. Diagnoses of all 11 species of Acroceratitis recorded from India along with an updated key to all described species is provided. DNA barcode sequences of A. sachini, A. parastriata David & Hancock, A. ceratitina (Bezzi), A. incompleta Hardy, A. histrionica (Meijere) and A. tomentosa Hardy were obtained and are reported. Phylogenetic analysis using mt COI revealed Acroceratitis to be monophyletic.